Innovation management in networked economies - Håkan Håkansson; Per-Ingvar Olsen (jbm - Journal of Business Market Management, 2012)
Business network research, service-dominant logic and service system thinking all reflect an interactional interpretation of value creation as the fundamental approach to understanding modern economies and business behavior. This paper aims at contributing to an integrative debate about innovation and value creation by analyzing innovation management challenges in relation to the interfaces between innovations and their environments in complex business landscapes. Any innovation may be seen as an entity within a multidimensional business landscape where relatedness, dynamism and variety are key dimensions. The innovation is typically positioned within some partly visible, partly invisible business landscape where it needs (1) to activate and stabilize a complex set of relationships between activities, resources and actors, (2) to systematically handle reactions to friction forces across these entities, and (3) to maintain and advance the necessary framing needed to coordinate interactions across all the involved and affected business resources, activities and actors. A general conclusion is that systematic managerial efforts appear to be the main driving force enacting and coordinating across these complex interfaces. In order for innovations to materialize, there is a critical need for some type of multi-functional, managerial network capable of recreating simplified and conceptual unity and a sense of direction while also managing the complexity, extendedness, ambiguity and multi-contextual challenges across the many complex interfaces.
urn:nbn:de:0114-jbm-v5i2.159
Keywords: 650; value co-creation; innovation management; business networks; system theory; relatedness; motion; variety; IMP; Innovationsmanagement; Unternehmensnetzwerk; Betriebliche Wertschöpfung; Systemtheorie